HUBUNGAN PENGETAHUAN KESEHATAN REPRODUKSI DENGAN PERILAKU PENCEGAHAN KEPUTIHAN PATOLOGIS PADA REMAJA PUTRI DI SMP NEGERI 1 TAPALANG BARAT - Rubiah R; Dewi Parwati; Norma Safitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Pathological vaginal discharge is a common reproductive health problem among adolescent girls. It is often caused by bacterial, fungal, or parasitic infections and is associated with inadequate reproductive health knowledge. Adequate knowledge is expected to encourage healthy preventive behaviors. Objective: To determine the relationship between reproductive health knowledge and preventive behavior toward pathological vaginal discharge among female junior high school students. Methods: A quantitative study with an analytical cross-sectional design was conducted among 60 female students selected using purposive sampling. Data were collected using validated questionnaires on reproductive health knowledge and preventive behavior. Data were analyzed using descriptive statistics and the Chi-Square test. Results: Most respondents had good knowledge (63.3%) and good preventive behavior (68.3%). Chi-Square analysis demonstrated a significant relationship between reproductive health knowledge and preventive behavior (p = 0.001). Conclusion: Reproductive health knowledge is significantly associated with preventive behavior toward pathological vaginal discharge among adolescent girls.